Bis{S-benzyl 3-[(phenyl)(pyridin-2-yl)- methylidene]dithiocarbazato}zinc acetonitrile monosolvate. - Begum, Thahira; Omar, Siti Aminah; Mohamed Tahir, Mohamed Ibrahim; Crouse, Karen Anne (International Union of Crystallography, 2012)
In the title compound, [Zn(C20H16N3S2)2]·CH3CN, two different Schiff base moieties coordinate to the central ZnII ion as tridentate N,N′,S-chelating ligands, creating a distorted octahedral environment [the smallest angle being 73.24 (6)° and the widest angle being 155.73 (7)°], with the two S atoms in cis positions. The dihedral angle between the mean planes of the two coordinating ligands is 83.65 (5)°. The crystal packing is consolidated by weak C—H(...)N hydrogen-bonding interactions.